THE ANALYSIS OF EDUCATIONAL EXPERTS TRAINING COURSES ON EDUCATIONAL ISSUES IN GERMAN-SPEAKING COUNTRIES OF THE EUROPEAN UNION - Ponomarenko, Natalia G. (Educological discourse, 2015)
The articles analyses educational experts training courses on educational issues in Germany, Austria and Switzerland, in particular Master's Programmes of " Developing School and Ensuring Quality" at the Free University of Berlin, "Educational process development and schools" at the Higher Pedagogical School of Freiburg, «Research and Development of School» at the University of Tuebingen and "School Development" at The Higher Pedagogical  Schools of Weingarten, Vorarlberg, Sankt-Gallen, Schaffhausen, Thurgau. The learning conditions for the courses stated above, the  amount of time allocated for each course and the main aspects of  educational experts training are determined.